Economic impact of COVID-19 on income and use of livelihoods related coping mechanisms in Chad - Kang, Yunhee; Wabyona, Edgar; Udahemuka, Francois Regis; Traore, Alladari; Doocy, Shannon (Frontiers in Sustainable Food Systems, 2023)
Impacts of the economic slowdown due to COVID-19 were prevalent in Sub-Saharan African countries. Using four nationally representative surveys collected in 2020 (rural n=13,208; urban n=1736) and 2021 (n=14,730; n=2231), this secondary analysis evaluates economic impacts of the pandemic on household income and use of livelihoods-related coping mechanisms in Chad. Univariate and multivariate regression, accounting for the survey design and sampling weights, was used to examine risk factors for reported income reduction and coping mechanism use and the associations with food expenditures and food security. The economic impact of COVID-19 was greater in urban areas than rural areas in 2020 with improvement in urban areas and deterioration in rural areas in 2021. The reported income reduction was associated with female and unmarried household heads, living in the Saharan zone, and in rural areas, non-agricultural income sources. In urban areas, having skilled/unskilled labor as the primary income source was protective. Risk factors for the adoption of livelihoods-related coping mechanisms were similar to those of income reduction, with findings related to poor living conditions. Income reduction due to COVID-19 was associated with the use of stress and crisis coping strategies and lower household expenditure in both years and poor food consumption in rural areas in 2020. This study elucidates the potential impact pathways of COVID-19 from a household economic downturn to limited food spending, poor food consumption, and increased use of coping mechanisms. Findings are relevant for informing the targeting of assistance in future economic shocks and suggest prioritizing socio-economically vulnerable households.